Core Stability Exercise Berbasis Dynamic Neuromuscular Stabilization Untuk Meningkatkan Endurance Pada Pemain Sepak Bola - Syafrianto, Donal; Liza, Liza; Alimuddin, Alimuddin; Andria, Yogi (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2022)
For soccer players, core stability and athletic performance are closely related. High levels of muscular endurance as well as heart and lung stamina are key factors in soccer players' athletic performance. The good functioning of the core stability muscle and the high endurance of soccer players will assist players minimize the risk of overuse injury, even if core stability plays a role in ensuring the balance of muscle work during exercise. Several training regimens place less emphasis on the strength of the core muscles, which leads to an imbalanced use of muscles during practice and competition. This is one of the things that makes players easily tired. This study's goal was to ascertain how core stability training based on dynamic neuromuscular stabilization affected soccer players' ability to play for longer periods of time. This study used an experiment with a one-group pretest and posttest design as its research method. The results demonstrated a correlation between improving endurance and increasing core stability muscle strength using the McGill core endurance test with a value of P = 0.000 and revealed that core stability training has an influence on increasing endurance with a value of P = 0.005. According to the study's findings, soccer players' endurance can be increased by using the Core Stability Exercise training approach, which is based on Dynamic Neuromuscular Stabilization.